A comparison of methods for the determination of the natural radioactivity content and radon exhalation. (October 2017) - de With, G.; Kovler, K.; Haquin, G.; Yungrais, Z.; de Jong, P.
Abstract: In this work a comparison of the activity content and radon exhalation rate of five concrete mixtures is carried out by NRG (NL) and SOREQ (IL) using the measurement standards applicable in the Netherlands and Israel, respectively. Comparison of the activity concentrations obtained by NRG and SOREQ for all concrete mixtures comply with proficiency requirements in literature and demonstrate that the results agree within a 99% confidence level. Variations in the weighted sum of the activity concentrations – computed according to the European and Israeli gamma indices – between the two laboratories are even smaller and well within the reported one standard deviation uncertainty. The measured radon exhalation rates agree within a confidence level of 90%, despite considerable differences in the applied methods and uncertainties in the material's radon exhalation that are beyond the measurement protocol. This includes the effects from humidity and aging, and it is mentioned that future guidance on the sample representativeness would be welcomed. Based on the findings of this work it is concluded that the methods for determining the activity concentration and the radon exhalation are equivalent methods and appropriate for testing of building materials that typically fall under radiation protection regulation. Furthermore, the methods can also be recommended for use in harmonised standards that are presently under development. Highlights: Activity concentrations and radon exhalation of concrete is measured using methods applicable in the Netherlands and Israel. The methods are equivalent and appropriate for testing building materials that fall under radiation protection regulation. The methods are on these grounds also suitable for use in harmonised standards that are presently under development.